Application of lean practices in small and medium-sized food enterprises. Issue 1 (6th January 2014) - Dora, Manoj; Van Goubergen, Dirk; Kumar, Maneesh; Molnar, Adrienn; Gellynck, Xavier
Abstract : Purpose: – Recent literature emphasizes the application of lean manufacturing practices to food processing industries in order to improve operational efficiency and productivity. Only a very limited number of studies have focused on the implementation of lean manufacturing practices within small and medium-sized enterprises (SMEs) operating in the food sector. The majority of these studies used the case study method and concentrated on individual lean manufacturing techniques geared towards resolving efficiency issues. This paper aims to analyze the status of the lean manufacturing practices and their benefits and barriers among European food processing SMEs. Design/methodology/approach: – A structured questionnaire was developed to collect data. A total of 35 SMEs' representatives, mostly CEOs and operations managers, participated in the survey. The study investigated the role of two control variables in lean implementation: size of the company and country of origin. Findings: – The findings show that lean manufacturing practice deployment in food processing SMEs is generally low and still evolving. However, some lean manufacturing practices are more prevalent than others; e.g. flow, pull and statistical process control are not widely used by the food processing SMEs, whereas total productive maintenance, employee involvement, and customer association are more widespread. The key barriers encountered by food SMEs in the implementation of lean manufacturing practices result from the special characteristics of the food sector, such as highly perishable products, complicated processing, extremely variable raw materials, recipes and unpredictable demand. In addition, lack of knowledge and resources makes it difficult for food processing SMEs to embark on the lean journey. Originality/value: – The gap in the literature regarding the application of lean manufacturing in the food sector is identified and addressed in this study. The originality of this paper lies in analyzing the current status of the use of lean manufacturing practices among food SMEs in Europe and identifying potential barriers.